Importance of Implantable Cardioverter‐Defibrillator Back‐Up in Cardiac Resynchronization Therapy Recipients: A Systematic Review and Meta‐Analysis. Issue 11 (November 2015) - Barra, Sérgio; Providência, Rui; Tang, Anthony; Heck, Patrick; Virdee, Munmohan; Agarwal, Sharad
Abstract : Background: It remains to be determined whether patients receiving cardiac resynchronization therapy (CRT) benefit from the addition of an implantable cardioverter‐defibrillator (ICD). Methods and Results: We performed a literature search looking for studies of patients implanted with CRTs. Comparisons were performed between patients receiving CRT‐defibrillator (CRT‐D) versus CRT‐pacemaker (CRT‐P). The primary outcome was all‐cause mortality. Data were pooled using a random‐effects model. The relative risk (RR) and hazard ratio (HR, when available) were used as measurements of treatment effect. Nineteen entries were entitled for inclusion, comprising 12 378 patients (7030 receiving CRT‐D and 5348 receiving CRT‐P) and 29 799 patient‐years of follow‐up. Those receiving CRT‐D were younger, were more often males, had lower NYHA class, lower prevalence of atrial fibrillation, higher prevalence of ischemic heart disease, and were more often on beta‐blockers. Ten studies showed significantly lower mortality rates with the CRT‐D device, while the remaining 9 were neutral. The pooled data of studies revealed that CRT‐D patients had significantly lower mortality rates compared with CRT‐P patients (mortality rates: CRT‐D 16.6% versus CRT‐P 27.1%; RR=0.69, 95% CI 0.62–0.76; P <0.00001). The number needed to treat to prevent one death was 10. The observed I 2 values showed moderate heterogeneity among studies (I 2 =48%). The benefit of CRT‐D was more pronounced in ischemic cardiomyopathy (HR=0.70, 95% CI 0.59–0.83, P <0.001, I 2 =0%), but a trend for benefit, albeit of lower magnitude, could also be seen in non‐ischemic dilated cardiomyopathy (HR=0.79, 95% CI 0.61–1.02, P =0.07, I 2 =36%). Conclusions: The addition of the ICD associates with a reduction in the risk of all‐cause mortality in CRT patients. This seems to be more pronounced in patients with ischemic cardiomyopathy.